Ofatumumab-mediated CD20+ B-cell depletion promotes neuromuscular junction functional recovery and sustains long-term efficacy in refractory generalized myasthenia gravis - Ren, Zhuangzhuang; Chen, Yuping; Liu, Yudan; Wang, Yan; Xu, Shengjie; Yang, Yanhua; Qiu, Feng (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to evaluate the long-term efficacy and safety of the fully human anti-CD20 monoclonal antibody ofatumumab in refractory generalized myasthenia gravis, with focus on its potential to promote recovery of neuromuscular junction transmission function.MethodsFourteen refractory patients treated at the Eighth Medical Center of the Chinese PLA General Hospital from March 2023 to June 2024 were included. All had relapsed after maintaining Minimal Manifestation Status for over 1 year and showed inadequate response to immunosuppressants. Ofatumumab 20 mg was administered at weeks 0, 1, 2, and 4, followed by additional doses every 4–6 months according to symptoms and CD19-positive B-cell reconstitution. Low-frequency 3-Hz repetitive nerve stimulation of the facial, accessory, and axillary nerves was conducted at baseline and month 12. MG-ADL, QMG, MGC scores and B-cell and T-cell levels were monitored.ResultsThe compound muscle action potential (CMAP) decrement of the predominantly involved nerve and the mean decrement across the three tested nerves improved at month 12, indicating enhanced neuromuscular junction transmission. MG-ADL, QMG, and MGC scores declined from month 1, with earlier improvement in bulbar, limb, and neck muscle groups. All patients discontinued corticosteroids by month 12 while remaining clinically stable. B cells stayed at low levels, whereas T-cell counts showed no significant change. Treatment was well tolerated.ConclusionOfatumumab provides durable clinical benefit and steroid-sparing effects, and its sustained depletion of CD20-positive B cells may facilitate recovery of neuromuscular junction transmission. These findings support its potential application within the field of regenerative pharmacology.